Diagnóstico de la Salud y Seguridad del trabajo en la Asociación de Emprendedores Agropecuarios “Chilla grande” de la Parroquia Canchagua, Cantón Saquisilì, Provincia de Cotopaxi, 2022-2022. - Gavilánez Fernández, Josselin Maribel (2022)
This project was conducted in the association of agricultural entrepreneurs “Chilla Grande” located in the parish of Canchagua, Cotopaxi Province, where the members of the association were characterized through socioeconomic and occupational risk indicators. The objective of this research was to determine the productive activities of the members of the association in order to identify the risks to which they are exposed during their daily workdays, and at the same time, to recognize the impact of how the Covid 19 pandemic has affected the members and their families. For this work, a survey was applied, which consists of two blocks of questions; in the first block, the members of the association were characterized socioeconomically and in the second block, the usual risks to which they are exposed were identified. As results, the following characteristics of the association were recognized: it is comprised of 12 women with an average age between 51-60 years old, and its main activity is agriculture, livestock and commerce. 66.7% of the members of the association consider that they are exposed to physical risk factors of heat, cold and sunlight during their working day. 58.3% of the associations members are regularly exposed to biological factors, the main one being mosquito bites, among other indicators evaluated. In terms of safety risks, more than 83.3% had accidents and injuries in the workplace, such as cuts, falls, blows, etc., with musculoskeletal consequences for the associates. The indicators measured in relation to the COVID-19 pandemic show that the level of exposure is 50 %, which are in low degree of contagion, however, some people who suffered from this disease were the result of activities outside their main work activity. In view of these results, a risk prevention plan was generated to protect the health of the workers and to attend to the problems derived from the work conditions.